Analisis Makna Visual Poster Film Anime "Suzume" - Arfin Tri Petra; Dwi Mutia Sari (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2025)
This study aims to analyze the visual meaning in the anime film poster Suzume using the visual semiotics approach by Kress and van Leeuwen, supported by Adi Kusrianto’s visual communication theory and Rustan’s visual elements. The research employs a qualitative descriptive method, focusing on typography, illustration, color, and layout. The findings show that the Suzume poster conveys a profound message through the combination of visual elements and semiotic structure. The transitional serif typography creates a classic and serious impression. The illustrations depict the main characters and symbols such as the door and chair, representing themes of journey, disaster, and personal growth. Dominant colors like blue, orange, white, and green evoke specific emotions and strengthen the visual message. The analysis based on visual metafunctions reveals that, representationally, the poster portrays the protagonist's mission to close disaster-causing doors. Interpersonally, it builds an emotional connection through the characters’ expressions and gestures. Compositionally, it demonstrates effective visual balance. In conclusion, the Suzume poster successfully conveys the film’s thematic message through strong and communicative visual design.